2005
DOI: 10.1016/j.jneuroim.2005.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Staphylococcus aureus-derived peptidoglycan (PGN) but not intact bacteria is mediated by CD14 in microglia

Abstract: Recognition of Staphylococcus aureus and its cell-wall component peptidoglycan (PGN) by microglia is mediated, in part, by Toll-like receptor 2 (TLR2). However, the pattern recognition receptor (PRR) CD14 can also bind PGN and enhance TLR2-mediated signaling in macrophages, suggesting a similar phenomenon might occur in microglia. To assess the functional significance of CD14 on microglial activation, we evaluated the responses of primary microglia isolated from CD14 knockout (KO) and wild type (WT) mice. PGN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 79 publications
4
25
1
Order By: Relevance
“…1, all three bacterial stimuli were found to enhance microglial MyD88 protein levels. As we had recently reported, TLR2 protein expression was elevated in response to S. aureus, PGN, and LPS in WT microglia (18,38) (Fig. 2).…”
Section: Quantitative Real-time Rt-pcr (Qrt-pcr)supporting
confidence: 78%
See 4 more Smart Citations
“…1, all three bacterial stimuli were found to enhance microglial MyD88 protein levels. As we had recently reported, TLR2 protein expression was elevated in response to S. aureus, PGN, and LPS in WT microglia (18,38) (Fig. 2).…”
Section: Quantitative Real-time Rt-pcr (Qrt-pcr)supporting
confidence: 78%
“…In our previous studies, we demonstrated that microglial proinflammatory mediator production was not attenuated in either TLR2 or CD14 KO microglia following S. aureus stimulation, suggesting the activation of alternative receptors (18,38). However, in the present work we have reported that cytokine/chemokine production in MyD88 KO microglia was nearly abolished in response to intact S. aureus.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations